INCREASING SHARIA FINANCIAL LITERATURE WITH ONLINE MEDIA DURING THE COVID-19 PANDEMIC (Case Study on SMEs Registered at the Department of Cooperatives and SMEs Bandung Regency) - Yayat Rahmat Hidayat; M Andri Ibrahim; Nanik Eprianti; Akhmad Yusup; Shakila Carisya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The Islamic financial literacy index in Indonesia is still low when compared to the conventional financial index, even though the majority of the population in Indonesia is Muslim. Therefore, efforts are needed to improve Islamic financial literacy so that people are more interested in Islamic financial products and services which will ultimately increase the market share of Islamic financial products and services. This study aims to analyze the increase in Islamic financial literacy in SMEs registered at the Department of Cooperatives and SMEs in Bandung Regency by using online media (zoom meeting). The method used is a two-mean difference test (paired sample t-test) between pretest and posttest. The results showed that the value of sig. (2-tailed) is 0.000 < α (0.05) and the t-count value is 28.787˃ t table is 2.093 (df=19 and 95% confidence level). Thus, it can be concluded that there is a significant average difference between the pretest and posttest. Keywords: Islamic financial literacy, online media, SMEs